Exploring Students' Perspective on Using Discord for Vocabulary Learning - Muhammad Adi Kurniawan; Rangga Adrianto; Diah Kurniati (Prominent, 2026)
Originally designed as a voice and text chat for gamers, Discord has evolved into a massive communication platform, yet its potential in formal language education remains largely unexplored. This study shifts the focus to its practical application in English learning, specifically zeroing in on a core question: how do third-semester students at the English Education Department (EED) of UMK perceive Discord as a viable medium for vocabulary acquisition? Rather than simply assuming the platform's utility, this research investigates the students' direct perspectives to understand if a casual social tool can function effectively in an academic context. To achieve this, the study employs a quantitative approach, utilizing a Google Form survey to gather concrete data. The assessment focuses on two main areas: the students' overall rating of their learning experience on the platform and their specific evaluation of Discord as a tool for mastering new vocabulary. By analyzing these student ratings, the article aims to move beyond theoretical possibilities and provide evidence-based insights. The expected findings will illuminate whether this mainstream app offers genuine educational value, highlighting both the general advantages of the platform and its specific impact on helping university students expand their English vocabulary.